2013
DOI: 10.1021/cm3037845
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Distribution of Supported Nanoparticles by Aqueous Synthesis

Abstract: Synthesis of supported nanoparticles with controlled size and uniform distribution is a major challenge in nanoscience, in particular for applications in catalysis. Cryo-electron tomography revealed with nanometer resolution the 3D distribution of phases present during nanoparticle synthesis via impregnation, drying, and thermal treatment with transition metal salt precursors. By conventional methods a nonuniform salt distribution led to clustered metal oxide nanoparticles (NiO, Co 3 O 4 ). In contrast, freeze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 42 publications
2
40
1
Order By: Relevance
“…We used macroscopic examination to indicate that complete pore filling was reached, as only at the very last drop all pores are filled and the system changes to a moist state, and pore filling during impregnation is thus not the origin of heterogeneity. Furthermore, different techniques have been reported previously that also confirm that pore filling was homogeneous after impregnation …”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…We used macroscopic examination to indicate that complete pore filling was reached, as only at the very last drop all pores are filled and the system changes to a moist state, and pore filling during impregnation is thus not the origin of heterogeneity. Furthermore, different techniques have been reported previously that also confirm that pore filling was homogeneous after impregnation …”
Section: Resultscontrasting
confidence: 76%
“…Additionally, for micrometer‐sized granules that are used typically for catalyst discovery on a laboratory scale, intraparticle variations in nanoparticle size, dispersion, and distribution have been shown. The use of electron tomography, for example, revealed that typical impregnation and drying results in a non‐uniform metal distribution and nanoparticle size, whereas optimization of drying and calcination resulted in a more homogeneous loading . However, to the best of our knowledge, studies on interparticle heterogeneities at the support granule level have only been reported twice: (1) advanced electron tomography on Pt‐loaded submicron USY zeolites and (2) a correlative approach by using optical microscopy on Ag‐loaded mesoporous silica granules .…”
Section: Introductionmentioning
confidence: 99%
“…Eggenhuisen et al performed freeze-drying on SBA-15 impregnated with nickel or cobalt nitrate by freezing in liquid nitrogen and drying at −55°C under reduced pressure. 79 Using cryo-TEM tomography to visualize the dried samples, it was shown that freeze-drying resulted in homogeneous distributions of cobalt nitrate after drying, whereas inhomogeneous distributions were obtained after conventional drying at 60°C (Figure 15). This difference in nanoscale distribution was largely maintained after a thermal activation was performed, illustrating the drying step is highly important for the final metal distribution at the nanoscale.…”
Section: Alternative Drying Methodsmentioning
confidence: 99%
“…A more detailed cryo-TEM tomography study was performed by Eggenhuisen et al on SBA-15 impregnated with cobalt nitrate or nickel nitrate solutions. 79 Although a few empty pores were found mainly on the external edge of the support particles, the majority were filled, and it was concluded that impregnation does lead to an almost homogeneous and complete pore filling. More quantitative measurements on larger samples by differential scanning calorimetry (DSC) have also provided evidence on the complete filling of porous supports ( Figure 8).…”
Section: Impregnationmentioning
confidence: 99%
“…For catalysts prepared via aqueous impregnation of porous oxide carriers, which is a route of high relevance for the manufacture of industrial catalysts, it has been shown that formation of high-metal-density domains or clusters of nanoparticles, can be controlled, or eventually prevented, through the choice of solvent or the addition of organic additives during the impregnation step [94,95]. In a recent study, Eggenhuisen et al [96] employed cryo-electron tomography to track the distribution of the metal (Ni and Co) nitrate precursors within the pores of an ordered silica mesostructure throughout different stages of catalyst synthesis and activation. The drying step following impregnation was identified as particularly influential for the ultimate metal distribution, and freeze-drying was proposed as an efficient approach to prevent metal redistribution and clustering.…”
Section: Recent Examples For the Use Of 3d Model Systems To Guide Catmentioning
confidence: 99%